Disruption of the β-catenin destruction complex via Ephexin1-Axin1 interaction promotes colorectal cancer proliferation - Jeeho Kim; Young Jin Jeon; In-Youb Chang; Jung-Hee Lee; Ho Jin You (Experimental and Molecular Medicine)
Abstract Wnt signaling is essential for cell growth and tumor formation and is abnormally activated in colorectal cancer (CRC), contributing to tumor progression; however, the specific role and regulatory mechanisms involved in tumor development remain unclear. Here, we show that Ephexin1, a guanine nucleotide exchange factor, is significantly overexpressed in CRC and is correlated with increased Wnt/β-catenin pathway activity. Through comprehensive analysis, including RNA sequencing data from TCGA and functional assays, we observed that Ephexin1 promotes tumor proliferation and migration by activating the Wnt/β-catenin pathway. This effect was mediated by the interaction of Ephexin1 with Axin1, a critical component of the β-catenin destruction complex, which in turn enhanced the stability and activity of β-catenin in signaling pathways critical for tumor development. Importantly, our findings also suggest that targeting Ephexin1 may increase the efficacy of Wnt/β-catenin pathway inhibitors in CRC treatment. These findings highlight the potential of targeting Ephexin1 as a strategy for developing effective treatments for CRC, suggesting a novel and promising approach to therapy aimed at inhibiting cancer progression.